2022
DOI: 10.1155/2022/2753294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella Sativa Oil on Oxidative Stress, Inflammatory, and Glycemic Control Indices in Diabetic Hemodialysis Patients: A Randomized Double-Blind, Controlled Trial

Abstract: Background and Aims. Diabetes is a leading cause of renal failure. High levels of oxidative stress and inflammation in patients with renal diabetes lead to various disorders and mortality. This study was performed to determine the effect of Nigella sativa (NS) supplementation on superoxide dismutase (SOD), malondialdehyde (MDA), total antioxidant capacity (TAC), high-sensitivity C-reactive protein (hs-CRP), glycosylated hemoglobin (HbA1c), fasting blood sugar (FBS), and insulin (INS) in patients with diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 45 publications
(47 reference statements)
0
24
0
Order By: Relevance
“…All the included trials had parallel designs and were published between 2012 and 2022. These studies were carried out in Iran ( 19 , 21 , 37 , 41 , 43 , 45 , 46 ), India ( 40 , 44 ), Egypt ( 20 ), and Saudi Arabia ( 42 ). In total, 666 participants (338 interventions and 328 controls) were recruited with the age range between 42.9 ± 3.2 and 56 ± 3.4 years old and the BMI range between 26.79 ± 2.94 and 33.90 ± 2.10 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the included trials had parallel designs and were published between 2012 and 2022. These studies were carried out in Iran ( 19 , 21 , 37 , 41 , 43 , 45 , 46 ), India ( 40 , 44 ), Egypt ( 20 ), and Saudi Arabia ( 42 ). In total, 666 participants (338 interventions and 328 controls) were recruited with the age range between 42.9 ± 3.2 and 56 ± 3.4 years old and the BMI range between 26.79 ± 2.94 and 33.90 ± 2.10 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies proposed N. sativa as an adjuvant therapy in diabetes control, since it revealed a significant reduction in glucose values following oral glucose tolerance test (OGTT), fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c) levels, and insulin resistance, and also an escalation in serum fasting insulin concentrations ( 18 20 ), while recent research reported that N. sativa supplementation increased the levels of glycemic control components ( 21 ). Furthermore, it has been demonstrated that N. Sativa extract could increase the high-density lipoprotein cholesterol (HDL-C) concentration through rising the activity of plasma lecithin cholesterol acetyltransferase (LCAT), and it could also exert its antioxidant effects by enhancing the activities of antioxidant enzymes, including catalase and glutathione peroxidase, leading to its potential efficacy in amelioration of atherosclerosis ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Persian medicine text book, several treatment principles are mentioned for the management of catarrh [ 20 ] and opium addiction [ 21 ]. Furthermore, a study by Rahmani et al showed that Nigella sativa oil was effective in reducing oxidative stress, inflammation, and blood sugar in diabetic patients [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there is a widespread tendency to use complementary and alternative medicine (CAM) therapies. It has been shown that the use of integrated methods of CAM and Western medicine can lead to better treatment results [ 11 18 ]. Persian medicine (PM), as one of the CAM methods, provides different strategies for the prevention and treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%